2020
DOI: 10.1021/acs.organomet.0c00476
|View full text |Cite
|
Sign up to set email alerts
|

Coordination and Reactivity Studies of Titanium Complexes of Monoanionic Inversely Polarized Phosphaalkene–Ethenolate Ligands

Abstract: The synthesis and reactivity of the first series of monoanionic bidentate ligands containing an N-heterocyclic carbene−phosphinidene adduct and their corresponding half-metallocene titanium complexes were investigated. The structural characterization of 5a confirmed bidentate coordination through the phosphorus and oxygen atoms of the ligand, with evidence of significant electron delocalization over the ligand structure. The new titanium complexes produced polyethylene at room temperature and under 1 atm of et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…In summary, the titanium phosphaalkene complexes show promising activities in polymerizations of olefins under ambient and mild conditions. 54 3.2. Ruthenium.…”
Section: Titaniummentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, the titanium phosphaalkene complexes show promising activities in polymerizations of olefins under ambient and mild conditions. 54 3.2. Ruthenium.…”
Section: Titaniummentioning
confidence: 99%
“…Performed DFT calculation revealed that the compound with Ti–P bond is thermodynamically competitive to the compound with Ti–C bond, however, the energies of transition state predicted that experimentally observed complex (Ti–C–P–N) is certainly kinetically favored (ΔΔ E = 11.4 kJ·mol –1 ) . In 2020, Lavoie et al reported the first titanium complexes ( 5A and 6A ; Scheme ) with monoanionic bidentate ligands containing an N -heterocyclic carbene-phosphinidene adduct ( 5 and 6 ) …”
Section: Synthesis Of D-block Element Phosphaalkene Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has been working with N-heterocyclic imines (NHI), a class of cyclic guanidines (and the related phosphorus analogues) derived from N-heterocyclic carbenes (NHC). These N-heterocyclic imines provide means to control the Lewis acidity of the metal center and of the coordination sphere through the NHC “building block” and the substituents on the endocyclic nitrogen atoms. We thus became interested in preparing a series of neutral bidentate ligands containing an acylated cyclic guanidine donor connected to a second donor fragment ( 1a–c ; Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Building on known protocols for the functionalisation of PH-bonds in primary imidazolio-phosphides ( IV , R′ = H) with strong electrophiles and base, 11,14 we set out to access a neutral analogue of III by condensation of 1 with bromoborane 2 in the presence of Et 3 N or DABCO ([2,2,2]-diazabicyclooctane). Borylated 3 was formed as anticipated, but the reaction was unselective, furnishing PH 3 , P 2 H 4 and imidazole/NHB-decorated derivatives thereof along with imidazolium ions and intractable solids as further products (Scheme 1).…”
mentioning
confidence: 99%